Meta discourse Use in Thesis Abstracts: A Case of M.Ed. English Majors - Pandey, Gopal Prasad (Nepal Journal of Multidisciplinary Research, 2020)
A metadiscourse is an important linguistic resource that binds different parts of a text together and facilitates communication building relationships with audiences. This aspect of discourse analysis has gained a considerable attention in academic writing these days. The aim of this study was to identify the types of metadiscourses used in the thesis abstracts of M.Ed. English majors of Tribhuvan University (TU), Kathmandu, Nepal. It also aimed at investigating the distribution patterns of metadiscourse resources in their thesis abstracts. Following Hyland's (2005) metadiscourse taxonomy, a corpus of 20 master theses submitted to the Department of English Education, TU in the year 2019 was analyzed to identify the types of metadiscourse used in the abstracts. Relying on a quantitative data analysis followed by qualitative analysis, it was found that the number of interactive metadiscourse features was considerably higher in the corpus than the interactional metadiscourse markers. The most frequent types of metadiscourses used in the texts were endophoric markers, transitions, boosters self mentions, and code glosses. Understanding the uses and functions of metadiscourse academic writing is pivotal for EFL/ESL students, particularly for postgraduate students when they are writing their theses or research articles for publication.